Archimedes’ Balance Approach Applied to Buoyant Force - Kim, Sungki; Paik, Seoung-Hey (The Physics teacher)
The floating and sinking phenomenon related to buoyant force can readily be observed in everyday life and easily demonstrated to young students. However, many students believe that the buoyant force is determined by the object’s attributes, such as the shape (e.g., ship) or material (e.g., wood). As a result, students find it challenging to understand that buoyant force changes when different volumes of the same object are submerged in water, or when the same object is submerged in different fluids. In response to the question concerning whether the weight of a cup changes when a tea bag is placed in a cup of water, 63.3% of first-year university students who majored in physics or chemistry were wrong. The problems related to buoyant force are difficult to understand even for college students, so the topic is used in the selection process for gifted students. Although numerous educational attempts have been made to help students understand the concept, buoyant force is still a difficult concept for them. Thus, an easy and clear approach to help students understand the buoyant force is desirable.